Interest rate rules and inflation risks in a macro‐finance model. (14th December 2021) - Horvath, Roman; Kaszab, Lorant; Marsal, Ales
Abstract: Long‐term bond yields contain a risk premium, an important part of which is compensation for inflation risks. The substantial increase in the Fed funds rate in the mid‐2000s did not raise long‐term US Treasury yields due to the reduction in the term premium (so‐called Greenspan conundrum) which was typically thought to be exogenous for monetary policy. We show using a New Keynesian macro‐finance model that the term premium is endogenous and is greatly influenced by the specification of the Taylor rule. Finally, we estimate our model using various specifications of Taylor rule on US data in 1961–2007 by the generalized methods of moments and evaluate the performance of our model.